The generation mechanism underlying the career decision-making difficulties faced by undergraduates in China during the COVID-19 pandemic: a qualitative study based on SCCT theory - Shi, Hairong (Frontiers in Psychology, 2023)
As COVID-19 continues to spread worldwide, the record number of graduates in China and pressure resulting from the economic downturn have led to low confidence in employment among college students, and the difficulties associated with career decision-making have gradually developed into a psychological barrier to the successful employment of Chinese college students. Using the “purposive sampling” approach to qualitative research, this study selected 20 undergraduates exhibiting delayed employment from a university as our research sample and used the career self-management model of social cognitive career theory (SCCT) as an analytical framework to conduct semistructured interviews with the aim of exploring influencing factors associated with and generation mechanism underlying the career decision-making difficulties experienced by Chinese undergraduates during the COVID-19 pandemic. According to the career self-management model of SCCT theory, the four variables of individual, parents, peers and social environment influence Chinese undergraduates’ career decision-making difficulties. On this basis, this study proposes a multivariable and single-subject generation mechanism to explain undergraduates’ career decision-making difficulties and tries to explicate the mental changes associated with the career decision-making difficulties encountered by undergraduates exhibiting delayed employment by reference to mind sponge theory.